FORMULASI DAN EVALUASI MASKER GEL PEEL-OFF EKSTRAK MINYAK BUAH MERAH PAPUA (Pandanus conoideus Lam) UNTUK PERAWATAN KULIT WAJAH - Fajar Setiawan; Saka Bekti Subagja; Anna Yuliana; Lusi Nurdianti (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Papua red fruit (Pandanus conoideus Lam) is one species of the genus Pandanus that grows naturally almost all over the land of Papua that has strong antioxidant potential that is widely applied in skin care. The purpose of this study was to find out the formulation of preparation making and evaluation of peel-off gel masks using variations in the concentration of papua red fruit oil extract. Methods used to make peel-off gel mask formulas to obtain high-quality preparations through evaluation stages include organoleptic testing, homogeneity, pH, spread test, dry power test, skin irritation test, viscosity test, and hedonic testing. The results showed that the preparation of peel-off gel mask extract of papua red fruit oil was successfully developed with good physical stability from the results of evaluation testing. The best peel-off gel mask formula in the study was a formula with a concentration of Papua red fruit oil extract of 0.5%b/v.